2004
DOI: 10.1111/j.0906-6705.2004.00269.x
|View full text |Cite
|
Sign up to set email alerts
|

Pimecrolimus – an anti‐inflammatory drug targeting the skin

Abstract: Pimecrolimus is the most recent member of calcineurin inhibitors available for the therapy for inflammatory skin diseases. It targets T-cells and mast cells and inhibits the production and release of cytokines and other inflammatory mediators, as well as the expression of signals essential for the activation of inflammatory T-lymphocytes. Pimecrolimus has a cell-selective mode of action. In contrast to corticosteroids, it does not affect, e.g., Langerhans'cells/dendritic cells (LC/DC), as demonstrated in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
0
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(93 citation statements)
references
References 50 publications
2
84
0
7
Order By: Relevance
“…Its mode of action is more selective than corticosteroids, and it was shown that pimecrolimus decreases significantly microcirculation and transepidermal water loss, whereas skin hydration increases in patients with AD (13). Topically pimecrolimus is generally well tolerated even on sensitive skin areas such as the face and neck (14)(15)(16). Intermittent treatment of AD with PIM at first signs and symptoms allows an effective control of the disease and reduces the need for TCS (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Its mode of action is more selective than corticosteroids, and it was shown that pimecrolimus decreases significantly microcirculation and transepidermal water loss, whereas skin hydration increases in patients with AD (13). Topically pimecrolimus is generally well tolerated even on sensitive skin areas such as the face and neck (14)(15)(16). Intermittent treatment of AD with PIM at first signs and symptoms allows an effective control of the disease and reduces the need for TCS (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Despite a high degree of structural similarity ( Fig. 1), pimecrolimus and tacrolimus display characteristic differences in terms of pharmacological profile (Stuetz et al, 2001;Meingassner et al, 2003;Grassberger et al, 2004;Bavandi et al, 2006;Kalthoff et al, 2007), and physicochemical and pharmacokinetic properties. Regarding physicochemical properties, the higher lipophilicity of pimecrolimus is noteworthy: pimecrolimus features an 8-fold higher octanol-water distribution coefficient than tacrolimus (Billich et al, 2004).…”
mentioning
confidence: 99%
“…A bőrben vagy a keringésben nem raktározódik el, így sem rövid, sem hosszú távon nincs szisztémás hatása. A pimecrolimus a helyi kortikoszteroidokkal és a tacrolimussal hasonló mértékben penetrál a bőrbe, szisztémás hatás lehetősége gyulladt bőrön történő alkalmazás esetén is minimális (10).…”
Section: Farmakokinetikaunclassified